A futuristic perspective on human-centric assembly. (January 2022) - Wang, Lihui
Highlights: Outlines a futuristic perspective on human-centric assembly. Identifies four enhanced human abilities to empower a human operator physically and intellectually. Introduces brain robotics driven by human brainwaves to assist human-centric assembly. Identifies current challenges and future opportunities in this research field. Abstract: This paper provides a futuristic perspective on human-centric assembly and identifies four enhanced human abilities to empower human operators. Brain robotics is also introduced to be a central element in human-centric assembly. Remaining challenges and future opportunities are also highlighted in the end.